Magnetic field measurement system in vertical status for superconducting undulator cooled in Dewar. (1st September 2022) - Chen, Zilin; He, Ping; Li, Yuhui; Yang, Xiangchen; Wei, Junhao; Zhang, Xiangzhen; Bian, Xiaojuan
Abstract: Superconducting undulators (SCUs) for advanced light sources are being developed rapidly to emit light with higher brightness and flux. The SCU consists of two superconducting magnets with a small gap, each with alternating poles. The SCU is invisible when operating in a Dewar or cryostat, so measuring the magnetic field in the narrow magnetic gap is a challenge in the development of the SCU. This paper presents a measurement system in vertical status for scanning the magnetic field of the SCU along the z-axis. The SCU is immersed vertically in 4.2 K liquid helium in a Dewar and the scanning is powered by a servo motor at room temperature. The measurement system overcomes the temperature difference of 300 K to drive the Hall probes to scan the magnetic field in the narrow magnetic gap of the SCU. In order to make the scanning area of the Hall probes coincide with the trajectory of the electron beam, a lot of detailed work on mechanical aspects has been done, such as controlling the positional accuracy of the Hall probes as they move, high precision machining and limiting the direction of movement. Unlike the currently reported magnetic field scans in the vertical status which are only available for SCU mock-ups of few periods, this system supports magnetic field measurements for SCUs up to 1.5 m long. The measurement system was validated on a 20-period SCU prototype, and after modification, the magnetic field of a liquid helium-cooled 30.5-period SCU was scanned. When the excitation current of the SCU with a magnetic gap of 7 mm is 450 A, the system measured a field distribution with a peak magnetic field of 1 T. The measurement system completed a full stroke trial run of 1750 mm before the 1.5 m SCU was machined. The results of magnetic field measurement from scanning in vertical status can be used as a reference for local shimming and correction of the magnetic poles of the SCU. This work establishes the SCU's ability to operate in cryostat horizontally.